A influência da matriz de oferta de energia elétrica do brasil nas emissões de GEE na fabricação e reciclagem de baterias de veículos elétricos - Mendes, Rodrigo de Oliveira (Universidade do Vale do Rio dos Sinos, 2023)
This research addresses the growing concern of resource scarcity and environmental degradation due to escalating natural resource demand and waste generation. It highlights the urgent need to transition from the linear model to a circular economy to mitigate the adverse impacts of industrial production. The focus of the study is on the electric vehicle (EV) industry, which is rapidly growing and its contributing to greenhouse gas emissions. The research emphasizes the importance of recycling EV batteries within a circular model to reduce emissions, preserve valuable materials, and meet the growing demand for batteries. It also explores the influence of the electricity generation mix in Brazil compared to China on recycling emissions. The study utilizes the Everbatt model to analyze the environmental and cost aspects of recycling lithium-ion batteries for passenger EVs, providing valuable insights for decision-makers and potential investors in the battery recycling industry. Additionally, this work identifies opportunities for improvement in battery recycling based on circular models and their managerial implications.
Keywords: Economia circular; Reciclagem de baterias; Veículos elétricos; Emissões de gases de efeito estufa; Escassez de recursos; Baterias de íon de lítio; Tecnologia de reciclagem; Circular economy; Battery recycling; Electric vehicles; Greenhouse gas emissions; Resource scarcity; Lithium-ion batteries; Recycling technology; ACCNPQ::Ciências Sociais Aplicadas::Administração